PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Wibisono, Seto; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test empirically test the influence of budget implementation whichis based on the performance to the accountability performance of government institution of Surabaya city, in order to see the influence of the implementation of budget based on performance to the accountability performance of government institution, it can be done by using three variables i.e. budget planning (PA), budget implementation (IA) and budget responsibility (PJA).In this research, the samples are 132 people from 22Local Apparatus Work Unit (SKPD) which consists of Local Government Budgeting Team (TAPD) which is involved in the budget planning of Surabaya local government. The data collection has been done by issuing questionnaires to the respondents. The data analysis of this research has been done by usinh multiple linear regressions analysis model. The result of this research shows that these three variables which are budget planning (PA), budget implementation (IA) and budget responsibility (PJA) have positive influence to the accountability performance of government institutionKeywords:based budget implementation, budget planning, budget implementation, budget responsibility, accountability government institution performance.